2012
DOI: 10.1038/clpt.2012.170
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Juice and Pomegranate Extract Do Not Impair Oral Clearance of Flurbiprofen in Human Volunteers: Divergence From In Vitro Results

Abstract: Nutrient interactions with prescription drugs is a topic of ongoing basic and clinical research. Pomegranate (POM) juice, and a 1-gram capsule containing POM extract, were evaluated in vitro and in vivo as inhibitors of CYP2C9, with flurbiprofen serving as the index substrate. Fluconazole was the positive control inhibitor. The in vitro 50% inhibitory concentrations (IC50) for POM juice and extract were below 1% (v/v), with no evidence of mechanism-based (irreversible) inhibition. In clinical studies, flurbipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…P or HFD ? GT values were reported and expressed as foldbasal (n = 11) *P \ 0.05 versus CTRL, P \ 0.05 versus HFD Eur J Nutr Pomegranate and green tea extracts do not protect mice against HFD-induced obesity In human studies, the typical dose used for pomegranate extracts is about 1 g/day [25][26][27] and between 300 mg and 4 g/day for green tea extracts [28,29], which corresponds to 5-65 mg/kg body weight/day. Considering species differences, this corresponds roughly to 500 mg of extracts/kg body weight/day in mice [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…P or HFD ? GT values were reported and expressed as foldbasal (n = 11) *P \ 0.05 versus CTRL, P \ 0.05 versus HFD Eur J Nutr Pomegranate and green tea extracts do not protect mice against HFD-induced obesity In human studies, the typical dose used for pomegranate extracts is about 1 g/day [25][26][27] and between 300 mg and 4 g/day for green tea extracts [28,29], which corresponds to 5-65 mg/kg body weight/day. Considering species differences, this corresponds roughly to 500 mg of extracts/kg body weight/day in mice [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical interaction potential for mechanismbased inhibitors is higher than that for reversible inhibitors, because restoration of P450 activity is dependent on de novo protein synthesis rather than removal of the perpetrator compound(s) (Watanabe et al, 2007). For example, MBI has been hypothesized as the only means by which fruit juices can elicit clinically significant interactions with CYP3A substrates (Hanley et al, 2012). Whereas the maximum rates of rCYP3A4 inactivation by silybin A and silybin B were roughly half those reported for a major mechanism-based inhibitor in grapefruit juice, DHB (;0.20 versus 0.41 min 21 ) (Paine et al, 2004), the K I s for silybin A and silybin B were ;100 times greater than those for DHB (;100 versus 1.1 mM).…”
mentioning
confidence: 99%
“…Also, PJ has been shown to inhibit cytochrome P450 3A (CYP3A), an enzyme involved in the regulation of blood vessel tone. However, unlike grapefruit juice, pomegranate juice has not been shown to inhibit drug clearance in humans by suppression of CYP3A [35] or CYP2C9 [36]. Moreover, multiple studies have shown that PJ also has anticancer [27, 37] and antimicrobial properties [38].…”
Section: Resultsmentioning
confidence: 99%